Impact of the Phenomenon of Social Class Mobility on the Consumer Buying & disposal Behaviour in Indian Perspective : A Case Study of White Goods Market - Makkar, Urvashi (Indian Journal of Marketing, 2006)
Phenomenon of social mobility has affected the consumption pattern and consumer-buying behavior in different social classes in India. Specifically in white goods category, this phenomenon is clearly evident since in the beginning of 21st century. Besides, it has also affected the disposal of the white goods in a very unique manner. Some form of Social Class structure or Social Stratification has existed in all societies throughout the history of human existence. In contemporary societies, an indication of the presence of social classes is the common reality that people who are better educated are more highly valued than those who are less educated or under-privileged.